Conceptions of Classroom Management in Education - Faizul Muna; Abid Nurhuda; Ana Maghfuroh; Nur Muhammad Lathif (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
Education aims to form quality human resources. So in the process of providing education, an institution must not only focus on providing adequate physical facilities and routines, but it must also fulfill the students' inner needs by preparing professional educational staff so that they can create a good learning atmosphere. fun in class and has a special skill called classroom management. This research aims to describe the concept of classroom management in education. The method used is qualitative with a literature study approach model, then concluded descriptively. The research results show that classroom management is a learning approach technique carried out by teachers to students according to the way they interpret classroom management itself. In general, it must be based on the principles of enthusiasm, warmth, variety, more emphasis on positive things, full of challenges, and instilling a spirit of discipline and flexibility. Meanwhile, the implementation of the classroom management conception in education includes class planning, class organization, class leadership in the sense of implementation, and finally class control in the sense of controlling and evaluating.